Health Care Quality Indicators Project Initial Indicators Report - Mattke, Soeren (OECD Health Working Papers, 2006)
The OECD Health Care Quality Indicator (HCQI) Project was started in 2001. The long-term objective of the HCQI Project is to develop a set of indicators that can be used to raise questions for further investigation concerning quality of health care across countries. It was envisioned that the indicators that were finally recommended for inclusion in the HCQI measure set would be scientifically sound, important at a clinical and policy level and feasible to collect in that data would be available and could be made comparable across countries. It was also envisioned that the indicators would not enable any judgement to be made on the overall performance of whole health systems. In essence, they should be used as the basis for investigation to understand why differences exist and what can be done to reduce those differences and improve care in all countries